2019
DOI: 10.1177/1756284819847034
|View full text |Cite
|
Sign up to set email alerts
|

EpidemIBD: rationale and design of a large-scale epidemiological study of inflammatory bowel disease in Spain

Abstract: Background: Inflammatory bowel disease (IBD) is associated with a considerable burden to the patient and society. However, current data on IBD incidence and burden are limited because of the paucity of nationwide epidemiological studies, heterogeneous designs, and a low number of participating centers and sample size. The EpidemIBD study is a large-scale investigation to provide an accurate assessment of the incidence of IBD in Spain, as well as treatment patterns and outcomes. Methods: This multicenter, popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…The reported prevalence in Spain is 205 cases per 100,000 inhabitants [5], although the accuracy of estimates in Europe is limited by small sample sizes. To address this problem in Spain, a nationwide prospective populationbased cohort study known as EpidemIBD was launched in 2017 to determine the true epidemiological scale of IBD [6].…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence in Spain is 205 cases per 100,000 inhabitants [5], although the accuracy of estimates in Europe is limited by small sample sizes. To address this problem in Spain, a nationwide prospective populationbased cohort study known as EpidemIBD was launched in 2017 to determine the true epidemiological scale of IBD [6].…”
Section: Introductionmentioning
confidence: 99%
“…In the nineties, the original IBSEN study was considered to represent the 'gold standard' of population-based cohorts. Since then many large-scale, well-characterized cohorts have been developed, all with their strengths and limitations [17][18][19][20]. The IBSEN III study has many advantages compared to other IBD cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…2 The EpidemIBD study aims to provide a detailed nationwide analysis of the incidence and outcomes of IBD in Spain. 3 The full results of the EpidemIBD study are yet to report, but early analyses of the cohort found an annual incidence of iron deficiency anemia (IDA) of 14.3–16.0 cases per 100,000 population per year. 4 , 5 …”
Section: Introductionmentioning
confidence: 99%